Effectiveness of Education Modules on Thalassemia Screening Awareness in Adolescents from Families with Thalassemia in Tegal City, Central Java: IN PRESS - Deddy Utomo; Anny Fauziah; Sri Hidayati; Nati Fatkhiyah (Jurnal Ilmu Kesehatan Masyarakat, 2026)
Thalassemia is a genetic disease that remains a public health problem in Indonesia, with a relatively high prevalence of carriers. Preventive measures through early screening for adolescents, especially those with a family history of thalassemia, are crucial. This study aimed to analyze the effectiveness of an educational module on increasing awareness of thalassemia screening among adolescents from families with thalassemia in Tegal City. The study used a quasi-experimental design with a one-group pretest-posttest approach. A sample of 120 adolescents was selected using purposive sampling. The intervention consisted of an educational module on thalassemia for two weeks. Data were collected using a screening awareness questionnaire and analyzed using a paired t-test. The results showed a significant increase in screening awareness scores from before (mean 58.3) to after the intervention (mean 82.7) with a p-value <0.001. The educational module was effective in increasing awareness of thalassemia screening among adolescents. Integration of the educational module into school- and family-based adolescent health programs is recommended.